Two solvatomorphic forms of a copper complex formulated as Cu( 1)(ClO4)2-1.2H2O and Cu(1)(ClO4)2, where 1 is 3,10-C-meso-3,5,7,7,10,12,14,14-octamethyl-1,4,8,11-tetraazacyclotetradecane - Nath, B.C. (2013)
Two copper complex solvatomorphs, namely (3,10-C-meso-3,5,7,7,10,12,14,14- octamethyl-1,4,8,11-tetraazacyclotetradecane)bis(perchlorato-κO)copper(II) 1.2-hydrate, [Cu(ClO4)2(C18H 40N4)]·1.2H2O, (I), and (3,10-C-meso-3,5,7,7,10,12,14,14-octamethyl-1,4,8,11-tetraazacyclotetradecane) bis(perchlorato-κO)copper(II), [Cu(ClO4)2(C 18H40N4)], (II), are described and compared with each other and with a third, already reported, anhydrous diastereomer, denoted (III). Both compounds present very similar centrosymmetic coordination environments, with the CuII cation lying on an inversion centre in a distorted 4+2 octahedral environment, defined by the macrocyclic N4 group in the equatorial sites and two perchlorate groups in trans-axial positions [one of the perchlorate ligands in (I) is partially disordered]. The most significant difference in molecular shape is seen in the orientation of the perchlorate anions, and the influence of this on the intramolecular hydrogen bonding is discussed. The (partially) hydrated state of (I) favours the formation of chains along [011], while the anhydrous character of (II) and (III) promotes loosely bound structures with low packing indices. © 2013 International Union of Crystallography.